L'Édifice Masonic Memorial Temple. Histoire et architecture maçonniques - Lauzon, Gilles (Ministère de la Culture, des Communications et de la Condition féminine et Direction du patrimoine et de la muséologie, 2010)
Keywords: Francs-Maçons

Les écrits urbains sous contrôle. L'exemple de Montréal - Artières, Philippe (Presses Universitaires de Rennes, 2014)
Keywords: Enseignes; Français; Publicité

"Le Canada est un païs de bois": Forest Resources and Shipbuilding in New France, 1660-1760 - Delaney, Monique (Université McGill, 2003)
The colonial contribution to the French naval shipbuilding industry in the seventeenth and eighteenth centuries, explored within the context of the forest from which the resources for the industry were taken, was a remarkably successful venture that came to an end with the onset of war. In the past, the end of the French naval shipbuilding industry in New France has been attributed to the action or inaction of France that resulted in the inefficient use of forest resources. Issues of interest in, organization or support of colonial efforts by France, however, were nevertheless, limited by the immutable realities of the colonial forest environment. This thesis argues that the success of the industry, considered within the appropriate context, is a consequence of colonial persistence in the face of constraints imposed by the colonial forest environment—despite these other significant issues. The official correspondence, written by colonial officials in New France, record colonial efforts to supply France with timber and detail the development of a naval shipbuilding industry in the colony. These documents provide source material for a case study that demonstrates the constraints imposed by the colonial forests on the experience of colonists, timber suppliers and shipbuilders. The colonial forest was not the same as the forests in France. A simple transfer of knowledge and practice from one forest to another was insufficient to deal with the differences in climate, forest age, tree species and the extent to which human activity affected the different forests. These differences challenged the way in which colonists could use forest resources for their own needs, for export to France and for naval construction. To consider this use of resources, without considering the differences between the available materials in the colony and those available in France, is to look at the story removed from the setting in which it took place. The unique forest in the colony was the setting in which colonial shipbuilding took place. Any study of the development of this industry, or any other industry that relied on forest resources, must give consideration to the constraints and realities of that forest.
Keywords: Construction navale

Déjouer l’ennui au fort de Ville-Marie à Montréal - Pothier, Louise (Revue d'histoire de la Nouvelle-France, 2023)
issued: 2023-21-00
Keywords: Archéologie; Forts

DUNLOP, ALEXANDER FRANCIS - Lachapelle, Jacques (Dictionnaire biographique du Canada, 2005)

Jardiner en Nouvelle-France - Tairraz, Monique (Continuité, 2003)
issued: 2003-23-00
Keywords: Jardins

Les incendies à Montréal sous le régime français - Massicotte, E.-Z. (Assurances, 1970)
Number: 4
Keywords: Incendies

L'île Sainte-Hélène sous le régime français - Perrault, Claude (Cahiers gen-histo, 1980)
Keywords: Île Sainte-Hélène

Les incendies à Montréal sous le régime français - Massicotte, E.-Z. (Bulletin des recherches historiques, 1919)
Number: 7
Keywords: Incendies

Images et figures du Montréal sous la France (1642-1763) - Lanctot, Gustave (Mémoires et comptes rendus de la Société royale du Canada, 1943)

Les lieux de justice à Montréal sous le Régime français - Robichaud, Léon (Le patrimoine bâti judiciaire de Montréal, 2018)
Keywords: Prisons; Tribunaux

Demeures et positionnement social dans les villes de la Nouvelle-France - Mercier-Méthé, Rosalie (Bulletin d'histoire politique, 2017)
Number: 1
Keywords: Logement

L’agriculture (péri)urbaine: tendances et dynamiques au Québec et en France - Bhatt, Vikram; Bryant, Christopher R.; Loudiyi, Salma (L’état du Québec 2011, 2011)
Keywords: Jardins

Les jardins d'agrément en Nouvelle-France. Étude historique et cartographique - Fortier, Marie-Josée (Les Éditions GID, 2012)
Keywords: Jardins

Jardins d'un autre temps. Deux jardins dans l'esprit de la Nouvelle-France - Tairraz, Monique (Maison Saint-Gabriel et Musée du Château Ramezay, 2001)
Keywords: Alimentation; Jardins; Maison Saint-Gabriel; Ramezay (château de)

Nouvel urbanisme, gentrification et mobilité quotidienne: leçons apprises des quartiers Plateau-Mont-Royal et Bois-Franc… - Barbonne, Rémy (La métropolisation et ses territoires, 2009)
Keywords: Gentrification; Navettage; Plateau Mont-Royal; Quartiers

Le secteur Bois-Franc à Saint-Laurent: l'évaluation environnementale stratégique du plan de réaménagement - Martin, Nadine; Waaub, Jean-Philippe (Les espaces dégradés: contraintes et conquêtes, 2000)
Keywords: Saint-Laurent (ville)

Les plans des villes de la Nouvelle-Orléans et de Montréal sous le régime français - Thouez, Jean-Pierre; Morissonneau, Christian (Annales de l'Université francophone d'été Saintonge-Québec, 1980)
Keywords: Cartes et plans

The Sociability of New Urbanism: A Comparative Study of Two Communities in Montreal, Angus Park and Bois-Franc - Pretula, Lesley (Université Concordia, 2003)
Keywords: Quartiers; Rosemont; Saint-Laurent (ville)

Animation et mise en valeur des quartiers historiques étude de cas: le quartier du Marais à Paris (France), le Vieux-Montréal (Québec) - Blais, Sylvie (Université du Québec à Montréal, 1986)
Keywords: Quartiers; Vieux-Montréal

Les plans en relief de la Nouvelle-France - Un état des questions sur les plans de Québec, de Montréal et de Louisbourg - Mayrand, Pierre (Revue d'histoire de l'Amérique française, 1968)
Number: 1
Keywords: Cartes et plans

Le Vieux-Port de Montréal - Une étape décisive pour un grand espace public - Adamczyk, Georges (ARQ - Architecture Québec, 1993)
Keywords: Vieux-port

Le Westmount Square - Montréal, 1964-1969 - Vanlaethem, France (ARQ - Architecture Québec, 1993)
Keywords: Gratte-ciel

Mies van der Rohe à Montréal - Bédard, Jean-François (ARQ - Architecture Québec, 1993)

Le Westmount Square - Les tribulations d'un projet - Vanlaethem, France (ARQ - Architecture Québec, 1993)
Keywords: Gratte-ciel

L'Île des Soeurs, «Le plus merveilleux domaine résidentiel en Amérique du Nord» - Cormier, Anne (ARQ - Architecture Québec, 1993)
Keywords: Île-des-Soeurs

Les poubelles du Québec : d'un enjeu de groupe de pression à un enjeu de mouvement social - Séguin, Michel; Maheu, Louis; Vaillancourt, Jean-Guy (Canadian Review of Sociology and Anthropology / Revue canadienne de sociologie et d'anthropologie, 1995)
Number: 2
Keywords: Groupes populaires

La station-service de l'Île des Soeurs - Bédard, Jean-François (ARQ - Architecture Québec, 1993)
Keywords: Île-des-Soeurs